Effects of gamal leaf extract (Gliricidia sepium Jacq.) on body weight and internal organ performance of mice (Mus musculus L.) - Harlis, Wa Ode; Malik, Nurhayu; Luvita, Luvita; Resman, Resman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Gamal leaves (Gliricidia sepium Jacq.) contain toxic compounds that have the potential to act as vegetable rodenticides, such as alkaloids, tannins, dicumerol, and hydrogen cyanic acid (HCN). Coumarin compounds can bind vitamin K, disrupt the circulatory system, and damage liver cells. The compounds dicumerol and warfarin are used as rat poison because of their anticoagulant properties, which prevent blood clots in the heart. Alkaloid and tannin compounds can damage liver cells through liver necrosis and bleeding in the digestive system. This study aims to determine the effect of Gamal leaf extract on body weight and internal organ performance in mice (Mus musculus L.). The experimental research method is based on a Completely Randomized Design (CRD) pattern. A total of 16 mice weighing 20-22 grams consisting of 4 treatments, namely A0 (water control), A1 (extract 10 mg/g BW), A2 (extract 15 mg/g BW) and A3 (extract 20 mg/g BW). The extract was given orally for 14 days, and body weight was measured every 3 days to obtain data on changes in body weight (PBB). At the end of the treatment, the mice were sacrificed using chloroform and then dissected to observe the performance of the liver, kidney and heart organs in color appearance and organ weight. Quantitative data were analyzed using one-way ANOVA and further DMRT test α=0.05. The research showed that mice's mean change in body weight (PBB) decreased significantly as the dose of Gamal leaf extract increased. The percentage of liver organ weight (BOH), kidney organ weight (BOG), and heart organ weight (BOJ) decreased as the dose of Gamal leaf extract increased. The research results concluded that Gamal leaf extract caused color changes in the internal organs of mice and significantly affected the percentage change in body weight (PBB) and internal organ weight (BOD) of mice along with increasing doses of Gamal leaf extract.